Are we on the side of over-diagnosis and treatment in BI-RADS 4A breast lesions? (Annals of Medical Research, 2021)
Aim: In BI-RADS 4A lesions, a malignancy rate of between 2% and 10% has been detected. Many patients avoid biopsy even though biopsy is recommended because of its low malignancy rates. The aim of this study is to investigate the need for biopsy of patients with BI-RADS 4A lesions.Materials and Methods: 392 patients classified as BI-RADS 4A in our hospital between January 2011 and December 2019 were retrospectively analyzed. Clinical and demographic characteristics of the patients, complaints, physical examination findings, USG (ultrasound), MMG (mammography) and magnetic resonance imaging (MRI) findings, invasive surgical procedure or noninvasive procedure performed, pathology results were analyzed. Results: The mean age was 44.29 years (range, 15–93 years). The most common complaint was palpable mass (36.5%). While 88.5% of examined pathologies were evaluated as benign lesions, 7.1% were malignant. The rate of malignancy increased with age, and this difference was statistically significant (p = .000). Malignancy increases with lesions size but it was not statistically significant (p = .052). Palpable mass was more common in malignant lesions (55.2%) (p = .014). Comparing the radiological evaluations of BI-RADS 4A lesions with the post-biopsy pathology results, size increase, more than three lobulations, border irregularities, and cystic areas did not make a statistically significant difference in terms of benign, premalignant, and malignant pathologies; however, intraductal localization was observed more frequently in benign and premalignant lesions than in malignant lesions, and this difference was statistically significant (p = .003).Conclusion: We anticipate that the criteria developed with this study (more than three lobulations, border irregularity, cystic areas, and intraductal locations), applied to a wide range of patients, can be a source for future studies and can be used safely in other clinics. As a result, we strongly recommend biopsy for patients with postmenopausal and palpable masses if the criteria we used for detecting BI-RADS 4A are also present.